Age-related positivity effect in emotional memory consolidation from middle age to late adulthood - Niu, Xinran; Utayde, Mia F.; Sanders, Kristin E. G.; Denis, Dan; Kensinger, Elizabeth A.; Payne, Jessica D. (Frontiers in Behavioral Neuroscience, 2024)
Background While younger adults are more likely to attend to, process, and remember negative relative to positive information, healthy older adults show the opposite pattern. The current study evaluates when, exactly, this positivity shift begins, and how it influences memory performance for positive, negative, and neutral information. Methods A total of 274 healthy early middle-aged (35–47), late middle-aged (48–59), and older adults (>59) viewed scenes consisting of a negative, positive, or a neutral object placed on a plausible neutral background, and rated each scene for its valence and arousal. After 12 h spanning a night of sleep (n = 137) or a day of wakefulness (n = 137), participants completed an unexpected memory test during which they were shown objects and backgrounds separately and indicated whether the scene component was the “same,” “similar,” or “new” to what they viewed during the study session. Results and conclusions We found that both late middle-aged and older adults rated positive and neutral scenes more positively compared to early middle-aged adults. However, only older adults showed better memory for positive objects relative to negative objects, and a greater positive memory trade-off magnitude (i.e., remembering positive objects at the cost of their associated neutral backgrounds) than negative memory trade-off magnitude (i.e., remembering negative objects at the cost of their associated neutral backgrounds). Our findings suggest that while the positivity bias may not emerge in memory until older adulthood, a shift toward positivity in terms of processing may begin in middle age.